Erosive potential of energy drink modified by calcium formulations on dental enamel: An in vitro study - Erik Vinícius Martins Jácome; Marquiony Marques dos Santos; Dayanne Monielle Duarte Moura; Patricia Bittencourt Santos; Maria do Socorro da Costa Inácio; Ana Clara Soares Paiva Torres (PLoS ONE, 2025)
Objectives To evaluate the erosive potential of an energy drink modified with different calcium formulations and concentrations on dental enamel. Methods This in vitro study used sixty dental enamel specimens, divided into 12 groups: traditional Red Bull ® energy drink modified with three concentrations each of calcium/phosphorus/potassium complex (0.71, 1.43, and 2.15g), dicalcium malate (0.83, 1.66, and 2.50g), and calcium citrate malate (1.26, 2.53, and 3.80g); unmodified traditional Red Bull ® energy drink; deionized water; and commercially available calcium-supplemented Life Mix Baixa Caloria ® orange juice. The pH of all drinks was measured using a pHmeter. Specimens were exposed to the drinks for two minutes. Surface roughness and microhardness were assessed before and after exposure using a contact profilometer and a Vickers microhardness tester, respectively. Results The addition of calcium/phosphorus/potassium complex increased the energy drink’s pH proportionally to the concentration added. Specimens exposed to modified drinks showed reduced roughness (p < 0.004) compared to control drinks. Drinks modified with 2.50g of dicalcium malate and 2.15g of the calcium/phosphorus/potassium complex significantly preserved enamel microhardness (p < 0.004) compared to the unmodified energy drink. Across all modifications, enamel surface microhardness loss was lower than in control groups, except for deionized water. Conclusion The addition of calcium formulations to the energy drink effectively reduced its erosive potential at all concentrations, with the calcium/phosphorus/potassium complex demonstrating the greatest protective effect.